2020
DOI: 10.1007/s12325-020-01251-y
|View full text |Cite
|
Sign up to set email alerts
|

Silymarin as Supportive Treatment in Liver Diseases: A Narrative Review

Abstract: Silymarin, an extract from milk thistle seeds, has been used for centuries to treat hepatic conditions. Preclinical data indicate that silymarin can reduce oxidative stress and consequent cytotoxicity, thereby protecting intact liver cells or cells not yet irreversibly damaged. Eurosil 85 Ò is a proprietary formulation developed to maximize the oral bioavailability of silymarin. Most of the clinical research on silymarin has used this formulation. Silymarin acts as a free radical scavenger and modulates enzyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
220
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 308 publications
(226 citation statements)
references
References 84 publications
4
220
0
2
Order By: Relevance
“…In recent studies, both silybin and 2,3-dehydrosilybin showed promising results not only prevention of chronic liver damage [10], but also in anti-inflammatory and antifibrotic therapies [1 In hepatic stellate cells (HSC), silybin decreased cell proliferation induced by platelet-derived grow factor (PDGF) and blocked de novo synthesis of collagen type I by reducing transforming grow factor-β1 (TGF-β) [12]. Furthermore, silybin and its congener silychristin inhibited IL-1β-induc formation of blood platelet-leukocyte aggregates in whole blood samples.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent studies, both silybin and 2,3-dehydrosilybin showed promising results not only prevention of chronic liver damage [10], but also in anti-inflammatory and antifibrotic therapies [1 In hepatic stellate cells (HSC), silybin decreased cell proliferation induced by platelet-derived grow factor (PDGF) and blocked de novo synthesis of collagen type I by reducing transforming grow factor-β1 (TGF-β) [12]. Furthermore, silybin and its congener silychristin inhibited IL-1β-induc formation of blood platelet-leukocyte aggregates in whole blood samples.…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, proposed cancer treatment regimens involve a new approach using natural compounds with limited or no cytotoxic effects on healthy cells, exploiting synergistic or adjuvant effects. Silybin is a typical example of such compound as it effectively inhibited overexpression of epidermal growth factor receptor (EGFR) and could be a potential target for therapeutic efficacy In recent studies, both silybin and 2,3-dehydrosilybin showed promising results not only in prevention of chronic liver damage [10], but also in anti-inflammatory and antifibrotic therapies [11]. In hepatic stellate cells (HSC), silybin decreased cell proliferation induced by platelet-derived growth factor (PDGF) and blocked de novo synthesis of collagen type I by reducing transforming growth factor-β1 (TGF-β) [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The internally produced glutathione and other enzymatic entities counteract the liver injury caused by the ROS, the reactive nitrogen-based species, and the produced oxidative stress. The oral supplementation of antioxidants for liver disorders has been studied, and several non-enzymatic antioxidants, (e.g., ascorbic acid, α-tocopherol, silibinin, naringenin, quercetin, curcumin, resveratrol, products of phenolic, flavonoid, tannin, and carotenoid types) have been exploited [ 21 , 22 , 23 ], and the plant-origin secondary metabolite-based antioxidants have revealed promising in vivo therapeutic effects on liver disorders in studied animal models [ 24 ], though clinical studies were deemed inconclusive [ 23 ]. However, the protective roles of these antioxidants on the liver, in experimentally induced-liver injury and toxication, have been investigated for various pure, single component natural products, and on the naturally-sourced plants’ extracts, as well as mixtures of synergistic natural products containing antioxidants of a structurally-varied chemical nature, and were found to be effective [ 9 , 25 , 26 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Silymarin is a flavonoid extract from milk thistle seeds that exhibits antioxidant and anti-inflammatory properties [ 72 ]. Silymarin has shown beneficial anthropometric, biochemical, and histologic effects in NAFLD patients [ 73 ]. In a trial involving 102 patients undergoing cardiac surgery, silymarin was shown to decrease postoperative proinflammatory cytokines (IL-6 and TNF-α) [ 74 ].…”
Section: Potential Therapies Targeting Nafld and Afmentioning
confidence: 99%